Isolated bulbar palsy and dysphagia in children with respiratory symptoms. (2nd October 2021) - Zimmels, Stacey; Balfour‐Lynn, Ian M; Christodoulou, Loucas; Pantazi, Mantha; Pavlidou, Efterpi; Pitt, Matthew; Kinali, Maria; Ismayilova, Naila
Abstract: Oropharyngeal dysphagia can cause chronic aspiration leading to significant respiratory symptoms. When dysphagia is diagnosed, an underlying cause is sought. We present a case series of 15 children diagnosed aged 6 months to 5 years (mean 2y 5mo; 11 males, four females) over a 6‐year period, who were found to have an isolated bulbar palsy on genioglossus electromyography, with no accompanying neurological or neurodevelopmental disorder. Eight children had dysphagia but a normal EMG. In those with isolated bulbar palsy, management included thickened fluids ( n =13), cooled boiled water ( n =1), and nasogastric tube feeding ( n =1). Follow‐up over 1 to 8 years (mean 5y) showed complete resolution in six children, improvement in four children, and no improvement in five children (including two requiring fluids via a gastrostomy). Eight children no longer had any respiratory symptoms. Isolated bulbar palsy is under‐recognized and has not been reported previously as a cause of significant dysphagia in children.